Elemental sulfur as a sulfuration agent in the copper-catalyzed C–H bond thiolation of electron-deficient arenes. Issue 39 (22nd September 2017) - Yan, Haiming; Huang, Zhiliang; Chen, Meng; Li, Cuiting; Chen, Ya; Gao, Meng; Lei, Aiwen
Abstract : By utilizing elemental sulfur as the thiolation agent and oxidant, a copper-catalyzed direct C–H bond thiolation of electron-deficient arenes was demonstrated. Abstract : By utilizing elemental sulfur as the thiolation agent and oxidant, a copper-catalyzed direct C–H bond thiolation of electron-deficient arenes was demonstrated. Various electron-deficient arenes were proved to be suitable for this transformation. Preliminary mechanistic studies indicated that this reaction underwent a radical pathway, in which the trisulfur radical anion (S3 ˙ − ) might play a vital role. Meanwhile, KIE experiments suggested that C–H bond cleavage was not involved in the rate-determining step.